How is Software Engineering Linked to Business? A Scopus-Based Bibliometric and Visualization - Almagribi, Ahmad Bilal; Ardianto, Fikky; Taufan, Anas; Kristomo, Domy (The Indonesian Journal of Computer Science, 2025)
Software engineering has significantly impacted various fields, including business, yet there had been no comprehensive bibliometric analysis of its interaction with business until this study. This research filled the gap by examining key contributors, affiliations, countries, and leading journals using a bibliometric analysis of 100 Scopus-indexed documents. The study revealed a peak in publications in 2008 with 11 documents, highlighting Gruhn, V. from Universität Leipzig, Germany, as the most prolific author. Both Germany and the United States were prominent, contributing 21 documents each. "Lecture Notes in Computer Science," along with its subseries, emerged as the most cited reference. The keyword analysis identified four main clusters focusing on the integration of IT, practical business applications, the role of education, and project management. The study recommends expanding research into Agile methodologies, UX Design, and technologies like AI, Cloud Computing, and IoT, providing insights into integrating software engineering into business strategies for future challenges.